2017
DOI: 10.1159/000477896
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging after Breast Oncoplastic Surgery: An Update

Abstract: Breast-oncoplastic surgery, allowing local tumor control and a better cosmetic outcome, is oncologically safe when applied to early-stage breast cancer. Breast cancer recurrence following conservative therapy may occur during the first 5 years after treatment, with a peak incidence after 2 years. Therefore, during the follow-up period, patients undergo a series of ultrasound (US) and mammographic examinations. However, after surgery and radiation therapy, several modifications occur in the treated breast, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…There are several methods that show high sensitivity for the detection of breast lesions, e. g. combined use of ultrasound (US) and mammography can reach sensitivity ranging from 92.6 % to 94.4 % in different studies, but with limited specificity in the differentiation of malignant from benign lesions of up to 67.9 % [1,2]. A similar tendency regarding contrast-enhanced MRI for breast lesions has been published, showing high sensitivity (94 %-100 %), especially for the assessment of tumor vascularity, but poor specificity regarding the differentiation of lesions (37-86 %) [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…There are several methods that show high sensitivity for the detection of breast lesions, e. g. combined use of ultrasound (US) and mammography can reach sensitivity ranging from 92.6 % to 94.4 % in different studies, but with limited specificity in the differentiation of malignant from benign lesions of up to 67.9 % [1,2]. A similar tendency regarding contrast-enhanced MRI for breast lesions has been published, showing high sensitivity (94 %-100 %), especially for the assessment of tumor vascularity, but poor specificity regarding the differentiation of lesions (37-86 %) [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…The most frequent complication was liponecrosis. Among different studies, the incidence of fat necrosis was, however, extremely variable, also depending on the lipofilling technique used (15)(16)(17). Usually liponecrosis is asymptomatic, sometimes patients may present local ecchymosis or a palpable mass.…”
Section: Discussionmentioning
confidence: 99%
“…Usually liponecrosis is asymptomatic, sometimes patients may present local ecchymosis or a palpable mass. On mammographic examination, liponecrosis may appear as a radiolucent rounded image surrounded by a thin radiopaque rib (16,17). The presence of calcifications on mammographic examination may lead to a suspicion of breast cancer relapse, especially at the first stage of the process when the calcifications present small size (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent survey by the European Society of Breast Imaging (EUSOBI) has shown that approximately 45 % of participants use MRI for the detection of LR after BCS [12]. This can lead to an increased number of false-positive findings, due to postoperative changes which may result in post-contrast enhancement on T1 sequences, such as early scarring, seroma, and fat necrosis [13,14]. Suspicious lesions detected by breast MRI are commonly assessed and biopsied under guidance of a targeted ultrasound (US) examination ("second-look" US) [15,16].…”
Section: Zusammenfassungmentioning
confidence: 99%